2014
DOI: 10.3892/mmr.2014.2148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and range of GJB2 and SLC26A4 mutations in patients with autosomal recessive non-syndromic hearing loss

Abstract: Abstract. The frequency and distribution of genetic mutations that cause deafness differ significantly according to ethnic group and region. Zhejiang is a province in the southeast of China, with an exceptional racial composition of the population caused by mass migration in ancient China. The purpose of the present study was to investigate the prevalence and spectrum of gap junction-β2 (GJB2), solute carrier family 26 (anion exchanger) member 4 (SLC26A4) and GJB3 mutations in patients with autosomal recessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
2
6
1
Order By: Relevance
“…Increasingly, many genetic studies have been adopted to identify genes involved in the initiation and progression of congenital deafness (Jiang et al, 2014;Dai et al, 2015;Zheng et al, 2015;Xia et al, 2016). We performed the case-control study described here to investigate the role of the GJB2 235delC and 30-35delG polymorphisms in susceptibility to this disease, finding that the GC and CC genotypes of the former were associated with increased risk, but that no such relationship was evident with the latter.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increasingly, many genetic studies have been adopted to identify genes involved in the initiation and progression of congenital deafness (Jiang et al, 2014;Dai et al, 2015;Zheng et al, 2015;Xia et al, 2016). We performed the case-control study described here to investigate the role of the GJB2 235delC and 30-35delG polymorphisms in susceptibility to this disease, finding that the GC and CC genotypes of the former were associated with increased risk, but that no such relationship was evident with the latter.…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations have reported that approximately 35% of patients with congenital deafness carry GJB2 233-235delC variants (Jiang et al, 2014;Dai et al, 2015;Zheng et al, 2015;Xia et al, 2016). These variations comprise the deletion of a cytosine residue in the GJB2 coding region at positions 233-235, leading to a frameshift mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling indicates that this alteration is located near the oligomer interaction domain, and thus may destabilize the hexameric connexon. Although this variant has not been previously reported, other variants at this codon (p.Trp44Cys, p.Trp44Ser) have been published in individuals with autosomal dominant nonsyndromic hearing loss (Denoyelle et al, ; Marziano, Casalotti, Portelli, Becker, & Forge, ), and another change at this codon, p.Trp44Leu, has been reported in a family with autosomal recessive nonsyndromic hearing loss (Jiang et al, ). Functional characterization of the p.Trp44Cys and p.Trp44Ser variants suggests that they have a dominant negative effect on wild‐type Cx26 and Cx30 (Martin, Coleman, Casalotti, Forge, & Evans, ; Marziano et al, ; Yum, Zhang, & Scherer, ).…”
Section: Discussionmentioning
confidence: 89%
“…According to a previous study, SLC26A4 bi-allelic pathogenic variants account for approximately 11% of Chinese Han probands with severe-to-profound HL and analysis of SLC26A4 in 176 unrelated Chinese patients with ARNSHL demonstrated that 13.6% (24/176) of patients carried at least one mutant allele [15]. In this study, 23.6% patients were found to have genetic defects in SLC26A4 , out of which, 20.1% carried bi-allelic pathogenic variants and 3.5% carried one mutant allele.…”
Section: Discussionmentioning
confidence: 99%